Możliwości wyboru formy opodatkowania małego przedsiębiorstwa w Polsce na przykładzie firmy “Hurt-Detal” w Nowym Sączu - Szmit, Agnieszka (My University, 2014)
Celem pracy jest analiza sytuacji finansowej firmy w Nowym Sączu, jak również możliwości wyboru formy opodatkowania dochodów tej firmy, prezentacja form opodatkowania małego przedsiębiorstwa oraz jego systemu ewidencyjnego. Rozdział pierwszy przedstawia system podatkowy w Polsce i zawiera podstawowe pojęcia związane z podatkiem, jego klasyfikacją i funkcjami. Rozdział drugi zawiera definicje i funkcje przedsiębiorstwa. W rozdziale trzecim możemy czytać o formach opodatkowania małych i średnich przedsiębiorstw.

The aim of the study was to analyze a financial situation of the company in Nowy Sacz as well as options of the form of taxation for this company, presentation of forms of taxation of small-sized enterprises and their accounting system. The first chapter presents the tax system in Poland and basic concepts related to tax, its classification and functions. The second chapter contains definitions and functions of the enterprise. In the third chapter we can read about forms of taxation of small and medium-sized enterprises.
Options of the Form of Taxation of a Small-Sized Enterprise in Poland on the Example of “Hurt-Detal” Company in Nowy Sacz
Keywords: podatek; rodzaje podatków; przedsiębiorstwo; funkcje przedsiębiorstwa; rodzaje ewidencji podatkowej; tax; types of taxes; enterprise; functions of the enterprise; types of the tax register